(untitled) (African Journal of Biomedical Research, 2023)
Dietary management is important in preventing complications associated with diabetes mellitus and enhancing quality of life. However, compliance to dietary recommendations among Diabetes Patients (DPs) remain unknown. This study was designed to assess the Knowledge, Attitude and Compliance (KAC) of Type 2 diabetic patients to dietary recommendation. This cross-sectional study involved 101 DPs attending Medical Outpatient Clinic at University College Hospital, Ibadan, Nigeria. A semi-structured, interviewer-administered questionnaire was used to obtain information on socio-demographic characteristics, diabetes history and KAC to dietary recommendation. Knowledge was assessed on a 26-point scale and categorized as good (≥18.0) and poor (<17.0). Attitude was assessed on a 34-point scale and considered as positive and negative at ≥27 and <27, respectively. Compliance was assessed on a 42-point scale and classified as good (≥29) or poor (<29). Data were analyzed and summarized as descriptive statistics and association among variables was determined using Chi-square test at p<0.05. Age of respondents was 56.9±11.6 years, 58.4% were female, 72.2% were married, and 11.9% had no formal education. About half (49.5%) of the participants had normal body mass index, 30.7% were overweight and 16.8% were obese. Diabetes duration was 9.4±5.7 years, 46.4% had family history of diabetes mellitus, and 93.1% relied on Dietitians for dietary plans. Patients on diet and drug, diet alone, and diet and insulin constituted 79.2%, 14.9% and 5.9%, respectively. Only 8.9% had normal blood glucose level and 31.7% were pre-diabetic. Mean fasting blood glucose value was 108.94±19.54mg/dL and 42.6% had co-morbidities including hypertension (25.7%), eye problem (7.9%), renal problem (5.0%) and ulcer (4.0%). Respondents with good knowledge, positive attitude and good compliance were 53.5%, 63.4%, and 77.2%, respectively/ Compliance with dietary recommendations was higher than observed knowledge and attitude levels of the respondents. Efforts should be intensified to strengthen compliance to reduce diabetes complications.